Tissue Flossing: A Commentary on Clinical Practice Recommendations - Scott W. Cheatham; Rusty Baker (North American Sports Medicine Institute, 2024)
Tissue flossing is an emerging myofascial intervention used by sports medicine professionals with a growing body of research evidence. Sports medicine professionals may use tissue flossing to increase myofascial mobility, improve joint ROM, enhance athletic performance, and reduce pain. Despite the increasing use, there is no consensus on clinical practice recommendations for this intervention. The purpose of this commentary is to discuss proposed clinical practice recommendations for tissue flossing and to encourage sports medicine professionals and researchers to contribute their expertise to further develop best practices. # Level of Evidence 5